1993
DOI: 10.1182/blood.v81.10.2744.2744
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 expression in human neutrophil and eosinophil peripheral blood granulocytes

Abstract: Human peripheral blood granulocytes were analyzed for expression of interleukin-6 (IL-6) using reverse-transcriptase polymerase chain reaction (RT-PCR) and in situ hybridization. Neutrophil granulocytes from healthy donors were shown to express variable levels of IL-6. This expression was rapidly down-regulated after the removal of the cells from the circulating blood. In vitro culture of neutrophils abolished IL-6 expression, which could be reactivated by addition of GM-CSF to the culture medium. Constitutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…2B). This finding can be explained by the IL-6 production of recently recruited neutrophils in PosC-SBP [19]. In recent studies, IL-6 was also shown to suppress neutrophil apoptosis via a platelet-activating factor-like mechanism [20,21].…”
Section: Association Of Il-6 Levels With Neutrophil Presencementioning
confidence: 90%
“…2B). This finding can be explained by the IL-6 production of recently recruited neutrophils in PosC-SBP [19]. In recent studies, IL-6 was also shown to suppress neutrophil apoptosis via a platelet-activating factor-like mechanism [20,21].…”
Section: Association Of Il-6 Levels With Neutrophil Presencementioning
confidence: 90%
“…Expression of Tnf and Ccl11 (encoding CC chemokine ligand 11, the cognate ligand for CCR3) did not significantly differ between IMQ-treated WT and DdblGATA mice ( Figure 4). Expression of Il6 and Il23 was lower in DdblGATA mice than in WT mice even without IMQ application ( Figure 4), suggesting that eosinophils are a cellular source of those inflammatory mediators (Guerra et al, 2017;Melani et al, 1993).…”
Section: Eosinophil Deficiency Protected Mice Against Imq-induced Psomentioning
confidence: 99%
“…Furthermore, when stimulated with eotaxin (CCL11) or RANTES (CCL5), human eosinophils rapidly release stored IL-4 by vesicular transport to the local milieu (46). Several other cytokines and chemokines are also transcribed and ⁄ or produced by eosinophils (3,31); for example, by reverse transcriptase polymerase chain reaction, constitutive expression of IL-6 and IL-10 mRNA was detected in blood eosinophils (44,45,47,48). Eosinophils also express a proinflammatory cytokine, TNF-a, and chemokines, such as MIP-1a (CCL3) and RANTES (CCL5) (49,50).…”
Section: Production Of Cytokines and Other Immunomodulatory Moleculesmentioning
confidence: 99%